The effects of tending cuttings on yield and value changes in black locust (Robinia pseudoacacia L.) stands: a case study - Rédei, Károly; Rásó, János; Ábri, Tamás; Keserű, Zsolt (Acta Agraria Debreceniensis, 2020)
Thinning experiments in black locust (Robinia pseudoacacia L.) stands have been carried out for many years in Hungary. This species has great economic importance in the timber supply of the country. This paper evaluates the effects of tending cuttings in two aspects: the effect on yield and stand value. The case study has proved that in black locust stands tending cuttings can not increase the periodic total production but the stem-quality index can be increased by 2%.